PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DENGAN GAYA KEPEMIMPINAN SEBAGAI MODERASI - Suprayitno, Anita Puspasari, Amin Wahyudi & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This is study aimed to determine the effect of work stress, leadership style on jobsatisfaction and job stress and work environments on job satifaction with leadershipstyle as modeation. Population in this study were 50 employees at the Board ofInvestment and Licensing Service of the Government of Sukoharjo district. This researchis a quantitative and qualitative research. Data collection techniques such asobservation, interviews and questionnaires. Data analysis using test instruments,classicassumption test, multiple linear regression analysis and the absolute value of thedifference. The results of this study show that there is a negative and significant effect ofwork stress on job satisfaction, there is a positive and significant impact on jobsatisfaction working environment, there is a positive and significant effect of leadershipstyle on job satisfaction, there variables contributed 42,5 percent and no significanteffect of work stress on job satisfaction with leadership style as moderating acontribution of 33,6 percent, no significant effect on job satisfaction workingenvironment with the style of leadership as moderating a contribution of 43,6 percent.Keywords: Job stress, work environment, leadership style, job satisfaction